Location selection of emergency logistics centers using an integrated dematel-ANP approach - (:unkn) unknown (World Scientific Publishing Co. Pte Ltd, 2012)
In this study, a location selection methodology using an integrated multi-criteria decision making approach for a logistics network model design in the presence of health emergency situations for Turkey is proposed. It is an important issue to urgent response to such unpredictable disasters. The proposed methodology tries to select the locations of temporary emergency centers for affected areas while considering eleven decision making criteria. Decision Making Trial and Evaluation Laboratory (DEMATEL) and Analytic Network Process (ANP) methods are integrated to determine the convenient locations considering the relations between criteria and alternative locations.